(3CZGfi GdUaG heZGfi GdehSjbis - (3GdJGOdj , EHQGgje Hf eMeO Hf YHO GdbGOQ GdMSfj GdWGdHj, CHh ESMGb,J (B1311 (3g` s
(3ChdgG (B:s
(3hHYO jbhd GdYHO deG JYGWjJ Ref GdTHGH bQGAI Ydhe GdQjGVI s
(3BNQgG (B:s
(3ceG CTGQ dPdc ai GdcJGH GdSGOS ef LeY GdLhGeY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B71s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdehSjbi hGdZfGAs